Policy Fluctuations and Their Impact on Quality Assurance in Higher Education in Nigeria - ODUKOYA, Adesola Afusat (Fakultas Pertanian, 2025)
Policy fluctuations have remained a critical challenge in managing higher education in Nigeria. This research investigates the impact of policy fluctuations on quality assurance in Nigerian higher education, a pressing issue amid ongoing educational reforms. The study evaluates how varying policy stability affects institutional performance and academic standards. Employing a descriptive survey design, the research involved case studies of five selected Nigerian universities, incorporating qualitative insights from interviews with stakeholders such as administrators, lecturers, and policymakers. Two hundred fifty respondents, including students and academic and non-academic staff, were surveyed using a self-designed questionnaire titled